A new H6 neutral point clamped transformerless photo voltaic inverter - Ahmad Syed; Xiaoqiang Guo; Sudhakar Babu Thanikanti; Mohammad Khishe (Scientific Reports)
Abstract Transformerless photovoltaic (PV) inverters are widely used in grid-connected solar energy systems due to their high efficiency and compact design. However, conventional transformerless inverters suffer from oscillating common-mode voltage (CMV), which leads to higher common-mode leakage current (CM-LC) due to the lack of galvanic isolation. This issue adversely affects system performance, safety, and compliance with grid standards. To address these challenges, this paper proposes a novel H6 Neutral Point Clamped (NPC) transformerless inverter topology, termed the H6-Diode (H6-D) topology, which integrates the advantages of AC-bypass low-loss switching and common-mode leakage current (CM-LC) elimination. The proposed topology features a clamping circuit that restricts the freewheeling voltage to half of the DC-link voltage, effectively minimizing CM-LC. The theoretical framework of the proposed design is rigorously validated through comprehensive simulations in MATLAB/Simulink and experimental verification using a laboratory prototype. The performance of the proposed inverter is evaluated based on key criteria, including common-mode voltage (CMV), common-mode leakage current (CM-LC), total harmonic distortion (%THD), switching and conduction losses, and overall efficiency. Compared to recent transformerless inverter topologies, the proposed H6-D topology demonstrates superior performance, achieving higher efficiency, lower THD, reduced voltage stress across components, and effective suppression of CM-LC. These results highlight its potential as a promising solution for high-performance grid-connected photovoltaic (PV) applications.